2015
DOI: 10.1155/2015/621237
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Effect of Electroacupuncture on Gene Expression in Hypothalamus of Rats with Stress-Induced Prehypertension Based on Gene Chip Technology

Abstract: Objective. To explore the effect of electroacupuncture (EA) on gene expression in the hypothalamus of rats with stress-induced prehypertension and try to reveal its biological mechanism with gene chip technology. Methods. The stress-induced hypertensive rat model was prepared by combining electric foot-shocks with generated noise. Molding cycle lasted for 14 days and EA intervention was applied on model + EA group during model preparation. Rat Gene 2.0 Array technology was used for the determination of gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…LR3 proved to be effective for treating hypertension. In stress-induced prehypertension model, needling at LR3 and Quchi (LI11) could reduce BP by targeting the gene expression of heart and hypothalamus [23, 24]. Consistent with previous studies, we selected LR3 and found that acupuncture significantly decreased the SBP, MBP, and HR in SHRs compared with WKYs, without any impact on normal BP.…”
Section: Discussionsupporting
confidence: 57%
“…LR3 proved to be effective for treating hypertension. In stress-induced prehypertension model, needling at LR3 and Quchi (LI11) could reduce BP by targeting the gene expression of heart and hypothalamus [23, 24]. Consistent with previous studies, we selected LR3 and found that acupuncture significantly decreased the SBP, MBP, and HR in SHRs compared with WKYs, without any impact on normal BP.…”
Section: Discussionsupporting
confidence: 57%
“…Activation of the DA receptor increases neurotrophic factor levels in experimental stroke, promoting tissue reorganization and plasticity [45]. EA at LR3 and LI11 bilaterally with a daily 20-min retention for 14 days in SIHRs affected the gene expression profile in the hypothalamus related to the contraction of vascular smooth muscles, concentrations of Ca 2+ , and the excitability of sympathetic nerves [46]. EA at ST36 in SIHRs reduced the BP via activation of GABA-A receptors (GABA = γ-aminobutyric acid) in the brain [47], leading to attenuation of neuronal death [48] and the removal of excessive neuronal excitability [49].…”
Section: The Potential Of Acupuncture For Secondary Prevention Of Strmentioning
confidence: 99%
“…Acupressure at point GV 20 activates the sympathetic nervous system, thereby stimulating the production of endorphins. In contrast, acupressure at LI 11 reduced the tyrosine hydroxylase activity to reduce pain, stress, and slow the heart rate (12), (17).…”
Section: Discussionmentioning
confidence: 99%